2021
DOI: 10.1007/s00431-021-04265-y
|View full text |Cite
|
Sign up to set email alerts
|

Preterm births in South-West England before and during the COVID-19 pandemic: an audit of retrospective data

Kate Maslin,
Roisin McKeon-Carter,
Joanne Hosking
et al.

Abstract: The COVID-19 lockdown had a series of intended and unintended consequences, including reduced infections and changes in activities and behaviours. Some of these changes may have been beneficial to perinatal outcomes; however, other factors such as reduced access to face-to-face healthcare may have contributed negatively to antenatal care. The aim of this audit was to evaluate neonatal admissions in the South-West of England during the COVID-19 pandemic in 2020 and the previous two years 2018–2019. Anonymised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Our results on preterm birth were consistent with data from several studies [ 5 , 27 , 29 , 40 , 41 , 42 , 43 , 44 ], although others report an increased risk of preterm delivery among pregnant women with SARS-COV-2 infection [ 4 , 32 , 33 , 37 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. However, Khalil et al suggest that, during COVID-19 disease, iatrogenic preterm delivery is increased rather than spontaneous [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results on preterm birth were consistent with data from several studies [ 5 , 27 , 29 , 40 , 41 , 42 , 43 , 44 ], although others report an increased risk of preterm delivery among pregnant women with SARS-COV-2 infection [ 4 , 32 , 33 , 37 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. However, Khalil et al suggest that, during COVID-19 disease, iatrogenic preterm delivery is increased rather than spontaneous [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in premature births in this study has been maintained even in the period of COVID-19 and, unlike our study, it did not affect the increase in stillbirths. 18 Contrary to some studies that reported a decrease in the hospitalization of premature babies during the lockdown period of COVID-19 at the beginning of the pandemic, 6,16,[19][20][21] a retrospective study on 46 neonatal intensive care units from 17 different countries, showed that the number of extreme preterm hospitalizations did not change significantly during the lockdown period. The selected countries were selected from different regions of Western and Eastern Europe, Asia, and North America, and there were no statistical differences between the levels of lockdown restrictions.…”
Section: Discussionmentioning
confidence: 84%
“…The decrease in premature births in this study has been maintained even in the period of COVID-19 and, unlike our study, it did not affect the increase in stillbirths. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, multiple studies and meta-analyses have highlighted the diverse effects of the COVID-19 pandemic on PTD, with potential influences from local factors and healthcare practices that could impact outcomes. A meta-analysis of non-US studies [29], some hospital and population-based studies in the United Kingdom (UK) [7,30] and Canada [31,32], one hospital-based study in Philadelphia [33], and a population-based study in California [34] spanning different time periods in 2020, found no changes in PTD rates at the onset of the pandemic. In contrast, several studies in different countries [35][36][37][38], one of which was among privately insured women [39], a population-based study in Tennessee [40], and another meta-analysis within this time period [41], also reported a decrease in overall PTD rates or in specific subgroups [42].…”
Section: Discussionmentioning
confidence: 99%